Ferrite composite material and preparation method and application thereof
Patent Information
- Application Number
- CN202311862545.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-29
AI Technical Summary
单一的W型铁氧体具有良好的磁损耗特性,但是其阻抗匹配过厚,导致微波吸收性能不好,严重制约了其在现实环境中的应用
[0019]本发明提供了一种铁氧体复合材料,包括W型铁氧体BaCo2Fe16O27和包覆在所述W型铁氧体BaCo2Fe16O27表面的纺锤状Fe2O3。本发明以纺锤状Fe2O3为阻抗匹配剂包覆在BaCo2Fe16O27表面,能够有效降低BaCo2Fe16O27的阻抗匹配厚度,并且与其他阻抗匹配剂相比具有更强的稳定性;并且Fe2O3纺锤状的形貌,具有大的长径比(长轴:短轴),有利于增强对电磁波的损耗。本发明提供的铁氧体复合材料(Fe2O3/BaCo2Fe16O27)作为吸波剂表现出良好的微波吸收性能,用于微波吸收领域具有良好的应用前景。
Smart Images

Figure CN118026278B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microwave absorbing materials technology, and in particular to a ferrite composite material, its preparation method, and its application. Background Technology
[0002] With the rapid development of electronic information transmission technology, microwave information brings convenience to people's lives, but also increases the risk of electromagnetic pollution and interference. Therefore, microwave absorbing materials are receiving increasing attention. W-type ferrites, with their complex spatial structure, tunable natural resonant frequency, and ease of preparation, are ideal magnetic microwave absorbers. While single W-type ferrites exhibit good magnetic loss characteristics, their excessively thick impedance matching leads to poor microwave absorption performance, severely limiting their application in real-world environments. Summary of the Invention
[0003] In view of this, the purpose of this invention is to provide a ferrite composite material, its preparation method, and its application. The ferrite composite material provided by this invention has excellent microwave absorption characteristics.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0005] This invention provides a ferrite composite material comprising W-type ferrite BaCo2Fe 16 O 27 and coated in the W-type ferrite BaCo2Fe 16 O 27 Spindle-shaped Fe2O3 on the surface.
[0006] Preferably, the spindle-shaped Fe2O3 has a mass of W-type ferrite BaCo2Fe. 16 O 27 The mass is 0-10%, and the mass of the spindle-shaped Fe2O3 is not 0.
[0007] This invention provides a method for preparing the ferrite composite material described above, comprising the following steps:
[0008] W-type ferrite BaCo2Fe 16 O 27 Powder, Fe 3+ A hydrothermal reaction is carried out with a mixture of salt, water, and ethylene glycol to obtain Fe₂O₃ / BaCo₂Fe. 16 O 27 Precursor;
[0009] The Fe2O3 / BaCo2Fe 16 O 27 The precursor is calcined to obtain the ferrite composite material; the calcination is carried out in an air atmosphere.
[0010] Preferably, the Fe 3+ The salt includes FeCl3·6H2O; the Fe 3+ Salt and W-type ferrite BaCo2Fe 16 O 27 The mass ratio of the powder is (1-5):4.
[0011] Preferably, the water and Fe 3+ The salt dosage ratio is 35 mL: 0.25 g; the volume ratio of ethylene glycol to water is (0-70): 35, and the volume of ethylene glycol is not 0.
[0012] Preferably, the hydrothermal reaction is carried out at a temperature of 100–150°C for 4–24 hours.
[0013] Preferably, the calcination temperature is 350–500°C and the time is 3–5 hours.
[0014] Preferably, the W-type ferrite BaCo2Fe 16 O 27 The powder preparation method includes the following steps:
[0015] (a) Barium nitrate, cobalt nitrate, ferric nitrate, water, and citric acid are mixed to form a sol-gel, resulting in a wet gel; the barium nitrate, cobalt nitrate, and ferric nitrate are respectively dissolved in Ba... 2+ Co 2+ and Fe 3+ The Ba 2+ Co 2+ and Fe 3+ The molar ratio is 1:2:15.3;
[0016] (b) The wet gel is dried and then calcined to obtain the W-type ferrite BaCo2Fe. 16 O 27 powder.
[0017] Preferably, in step (a) Ba 2+ Co 2+ and Fe 3+ The ratio of the total molar amount to the molar amount of citric acid is 1:(1~1.5). The calcination in step (b) includes a first calcination and a second calcination in sequence. The temperature of the first calcination is 450°C and the holding time is 3h. The temperature of the second calcination is 1300°C and the holding time is 3h.
[0018] This invention provides the application of the ferrite composite material described in the above technical solutions or the ferrite composite material prepared by the above technical solutions as a microwave absorber.
[0019] This invention provides a ferrite composite material comprising W-type ferrite BaCo2Fe 16 O 27 and coated in the W-type ferrite BaCo2Fe 16 O 27 Spindle-shaped Fe2O3 on the surface. This invention uses spindle-shaped Fe2O3 as an impedance matching agent to coat BaCo2Fe. 16 O 27 The surface can effectively reduce BaCo2Fe 16 O 27 The Fe2O3 ferrite composite material has a high impedance matching thickness and exhibits stronger stability compared to other impedance matching agents. Furthermore, its spindle-shaped morphology with a large aspect ratio (major axis:minor axis) is beneficial for enhancing electromagnetic wave loss. This invention provides a ferrite composite material (Fe2O3 / BaCo2Fe...) 16 O 27 As an absorbing agent, it exhibits excellent microwave absorption performance and has promising application prospects in the field of microwave absorption.
[0020] This invention provides a method for preparing the ferrite composite material described above. The preparation method provided by this invention is simple, low in cost, and easy to scale up for production. Attached Figure Description
[0021] Figure 1 BaCo2Fe prepared in Example 1 16 O 27 And the Fe2O3 / BaCo2Fe prepared in Examples 2-6 16 O 27 XRD curves of composite materials;
[0022] Figure 2 BaCo2Fe prepared in Example 1 16 O 27 And the Fe2O3 / BaCo2Fe prepared in Examples 2-6 16 O 27 Scanning electron microscope images of composite materials. Figure 2 (a) to (f) correspond to Examples 1 to 6, respectively;
[0023] Figure 3 Fe2O3 / BaCo2Fe in Examples 7-12 16 O 27 Reflection loss (RL) diagram of the absorbing agent. Figure 3 (a) to (f) correspond to Examples 7 to 12, respectively. Detailed Implementation
[0024] This invention provides a ferrite composite material comprising W-type ferrite BaCo2Fe 16 O 27 and coated in the W-type ferrite BaCo2Fe 16 O 27 Spindle-shaped Fe2O3 on the surface.
[0025] In this invention, the spindle-shaped Fe2O3 is preferably of W-type ferrite BaCo2Fe. 16 O 27 The mass of the spindle-shaped Fe2O3 is 0-10%, and the mass of the spindle-shaped Fe2O3 is not 0. More preferably, the mass of the spindle-shaped Fe2O3 is W-type ferrite BaCo2Fe. 16 O 27 5% of the quality.
[0026] This invention coats spindle-shaped Fe2O3 with BaCo2Fe 16 O 27 An impedance matching layer was formed on the surface, effectively reducing the impedance of BaCo2Fe. 16 O 27 Impedance matching thickness.
[0027] This invention provides a method for preparing the ferrite composite material described above, comprising the following steps:
[0028] W-type ferrite BaCo2Fe 16 O 27 Powder, Fe 3+ A hydrothermal reaction is carried out with a mixture of salt, water, and ethylene glycol to obtain Fe₂O₃ / BaCo₂Fe. 16 O 27 Precursor;
[0029] The Fe2O3 / BaCo2Fe 16 O 27 The precursor is calcined to obtain the ferrite composite material; the calcination is carried out in an air atmosphere.
[0030] First, the W-type ferrite BaCo2Fe 16 O 27 The powder is explained.
[0031] This invention relates to the W-type ferrite BaCo2Fe 16 O 27 The source of the powder is not particularly required; it can be obtained from commercially available products or prepared using methods well-known to those skilled in the art. In this embodiment of the invention, the W-type ferrite BaCo2Fe... 16 O 27 The preferred method for preparing the powder includes the following steps:
[0032] (a) Barium nitrate, cobalt nitrate, ferric nitrate, water, and citric acid are mixed to form a sol-gel, resulting in a wet gel; the barium nitrate, cobalt nitrate, and ferric nitrate are respectively dissolved in Ba... 2+ Co 2+ and Fe 3+ The Ba 2+ Co 2+ and Fe 3+ The molar ratio is 1:2:15.3;
[0033] (b) The wet gel is dried and then calcined to obtain the W-type ferrite BaCo2Fe. 16 O 27 powder.
[0034] This invention will use Ba 2+ Co 2+ and Fe 3+ The molar ratio was controlled at 1:2:15.3. The iron-deficient formulation was more conducive to the formation of pure-phase W-type ferrite, while Ba... 2+ Co 2+ and Fe 3+ The W-type ferrite generated with a molar ratio of 1:2:16 will contain impurity phases. In this invention, the Ba... 2+ Co 2+ and Fe 3+ The ratio of the total molar amount of the substance to the molar amount of citric acid is preferably 1:(1 to 1.5), more preferably 1:1.2. In this invention, the water is preferably deionized water. There are no special requirements for the amount of water used; it is sufficient to fully dissolve the barium nitrate, cobalt nitrate, ferric nitrate, and citric acid.
[0035] In this invention, the preferred specific operation of the sol-gel is as follows:
[0036] The barium nitrate, cobalt nitrate, and ferric nitrate were dissolved in water to obtain a mixed metal salt solution;
[0037] The citric acid was dissolved in water to obtain a citric acid solution;
[0038] The citric acid solution was slowly added dropwise to the mixed metal salt solution, and the mixture was stirred to form a sol.
[0039] The pH of the sol was adjusted to 6-7 and heated until a wet gel was formed.
[0040] In this invention, barium nitrate, cobalt nitrate, and ferric nitrate are preferably dissolved in water by ultrasonic dispersion. The stirring time is preferably 30 minutes. Citric acid acts as a complexing agent, forming a metal ion complex, and a sol is formed as the solvent evaporates during stirring. Ammonia is preferably used to adjust the pH of the sol to 6-7. The heating temperature is preferably 80°C, and water bath heating is preferred. The heating time is not particularly important, as long as a gel is formed. After the wet gel is formed, it is preferably allowed to stand at room temperature.
[0041] After obtaining the wet gel, the present invention dries the wet gel and then calcines it to obtain the W-type ferrite BaCo2Fe. 16 O 27 Powder. In this invention, the drying temperature is preferably 120–160°C, more preferably 150°C, and the drying time is preferably 12–36 h, more preferably 18–24 h; the drying is preferably carried out in an oven. After the drying process, the wet gel becomes a dry gel.
[0042] In this invention, the calcination preferably includes a first calcination and a second calcination sequentially. The temperature of the first calcination is preferably 450°C, and the holding time is preferably 3 hours. The temperature of the second calcination is preferably 1300°C, and the holding time is preferably 3 hours. The calcination is preferably carried out in an air atmosphere. The calcination is preferably carried out in a tube furnace, and the material is allowed to cool naturally after calcination. This invention removes organic matter such as citric acid from the dry gel through the first calcination; and through the second calcination, forms a W-type ferrite, BaCo2Fe. 16 O 27 powder.
[0043] The preparation of the ferrite composite material will now be described in detail.
[0044] This invention utilizes W-type ferrite BaCo2Fe 16 O 27 Powder, Fe 3+ A hydrothermal reaction is carried out with a mixture of salt, water, and ethylene glycol to obtain Fe₂O₃ / BaCo₂Fe. 16 O 27 Precursor.
[0045] In this invention, the Fe 3+ The salt preferably comprises FeCl3·6H2O; the Fe 3+ Salt and W-type ferrite BaCo2Fe 16 O 27 The preferred mass ratio of the powders is (1-5):4, more preferably (2-2.5):4. In this invention, the water and Fe... 3+The preferred salt ratio is 35 mL: 0.25 g; the volume ratio of ethylene glycol to water is (0-70):35, and the volume of ethylene glycol is not zero. A more preferred volume ratio is (16-70):35, and even more preferably (35-70):35; the water is preferably deionized water. In this invention, the addition of ethylene glycol allows Fe2O3 to exist in a spindle-shaped form. Ethylene glycol mainly affects the size and density of Fe2O3 growth. As the ethylene glycol content increases, Fe2O3 gradually grows larger and denser, increasing interfacial polarization and enhancing microwave absorption performance. Therefore, this invention can control the growth of Fe2O3 by adjusting the proportion of ethylene glycol added.
[0046] In this invention, the W-type ferrite BaCo2Fe 16 O 27 Powder, Fe 3+ The preferred method for mixing salt, water, and ethylene glycol is to: [The text abruptly ends here, likely due to an incomplete sentence or missing information.] 3+ Salt is added to water, and then the W-type ferrite BaCo2Fe is added to it. 16 O 27 After stirring the powder for 30 minutes, add ethylene glycol and continue stirring for another 30 minutes.
[0047] In this invention, the hydrothermal reaction temperature is preferably 100–150°C, more preferably 120°C, and the reaction time is preferably 4–24 h, more preferably 6–16 h, and even more preferably 12 h. In this invention, the hydrothermal time affects the size and coating density of Fe₂O₃. Preferably, the mixed solution obtained in this invention is transferred to a reaction vessel and then placed in an oven for hydrothermal reaction. During the hydrothermal reaction, Fe… 3+ Forced hydrolysis forms spindle-shaped FeOOH in BaCo2Fe 16 O 27 Material surface recrystallization.
[0048] Following the hydrothermal reaction, the present invention preferably involves naturally cooling the resulting reaction solution and then sequentially centrifuging, washing, and drying to obtain Fe2O3 / BaCo2Fe. 16 O 27 Precursor.
[0049] Fe2O3 / BaCo2Fe was obtained 16 O 27 Following the precursor, the present invention uses the Fe2O3 / BaCo2Fe 16 O 27The precursor is calcined to obtain the ferrite composite material. In this invention, the calcination temperature is preferably 350–500°C, more preferably 400°C, the heating rate to the calcination temperature is preferably 5°C / min, and the calcination time is preferably 3–5 h, more preferably 3 h; the calcination is carried out in an air atmosphere. In this invention, the calcination is preferably carried out in a tube furnace. During the calcination process, Fe2O3 / BaCo2Fe 16 O 27 FeOOH in the precursor is converted into Fe2O3.
[0050] This invention provides the application of the ferrite composite material described in the above technical solutions or the ferrite composite material prepared by the above technical solutions as a microwave absorber. The ferrite composite material (Fe2O3 / BaCo2Fe) provided by this invention... 16 O 27 As a microwave absorber, it exhibits excellent microwave absorption performance and has promising application prospects in the field of microwave absorption. This invention does not impose any special requirements on the application method; any application method well-known to those skilled in the art can be used. In this embodiment, the ferrite composite material and a binder are heated, melted, and pressed into a microwave absorbing material; the binder is preferably paraffin wax, as paraffin wax does not absorb electromagnetic waves, and the preferred mass ratio of the ferrite composite material to the binder is 0.21:0.09.
[0051] To further illustrate the present invention, the ferrite composite material, its preparation method, and its application provided by the present invention are described in detail below with reference to examples, but these should not be construed as limiting the scope of protection of the present invention.
[0052] Example 1: Preparation of BaCo2Fe 16 O 27
[0053] 0.2614 g of barium nitrate, 6.1812 g of ferric nitrate nonahydrate, and 0.5821 g of cobalt nitrate hexahydrate were dissolved in 70 mL of deionized water and sonicated to obtain a metal salt solution. 4.2194 g of citric acid was weighed and dissolved in 20 mL of deionized water to obtain a citric acid solution. The citric acid solution was slowly added dropwise to the metal salt solution, and the mixture was stirred for 30 min. Ammonia was added to adjust the pH to 7, and the solution was heated in a water bath at 80 °C until it changed from dark green to viscous. The solution was then allowed to stand until room temperature. The wet gel was transferred to an oven and dried at 150 °C for 12 h to obtain a dry gel. The dry gel was then transferred to a tube furnace and heated to 450 °C for 3 h, followed by calcination at 1300 °C for 3 h. After natural cooling, BaCo₂Fe₂ was obtained. 16 O 27 Powder.
[0054] The material prepared in Example 1 was scanned using an X-ray diffractometer, and the results are shown below. Figure 1 The material prepared is BaCo2Fe 16 O 27 .
[0055] The material prepared in Example 1 was observed using a scanning electron microscope, and the results are shown below. Figure 2 In (a), BaCo2Fe can be seen. 16 O 27 A typical hexagonal plate-like structure.
[0056] Example 2: Preparation of Fe2O3 / BaCo2Fe 16 O 27 Composite materials
[0057] (1) BaCo2Fe was prepared according to the steps in Example 1. 16 O 27 ;
[0058] (2) Place 0.25g FeCl3·6H2O in 35mL of deionized water, and then add 0.4g of BaCo2Fe prepared in step (1). 16 O 27 After mixing, stir for 30 minutes, add 35 mL of ethylene glycol, and continue stirring for another 30 minutes.
[0059] (3) After transferring the mixture from step (2) into the reactor, place it in a 120°C oven and keep it warm for 4 hours. After natural cooling, wash, centrifuge, and dry for 24 hours.
[0060] (4) The sample obtained in step (3) is placed in a tube furnace and heated to 400℃ at a rate of 5℃ / min, and held at that temperature for 3h to obtain Fe2O3 / BaCo2Fe. 16 O 27 The composite material is denoted as Fe2O3 / BaCo2Fe. 16 O 27 -4h.
[0061] The material prepared in Example 2 was scanned using an X-ray diffractometer, and the results are shown below. Figure 1 It is Fe2O3 / BaCo2Fe 16 O 27 Composite materials.
[0062] The material prepared in Example 2 was tested using a scanning electron microscope, and the results are shown in the figure. Figure 2 In (b), it can be seen that Fe2O3 is spindle-shaped and coated on BaCo2Fe. 16 O 27 surface.
[0063] Example 3: Preparation of Fe2O3 / BaCo2Fe 16 O 27 Composite materials
[0064] (1) BaCo2Fe was prepared according to the steps in Example 1. 16 O 27 ;
[0065] (2) Place 0.25g FeCl3·6H2O in 35mL of deionized water, and then add 0.4g of BaCo2Fe prepared in step (1). 16 O 27 After mixing, stir for 30 minutes, add 35 mL of ethylene glycol, and continue stirring for another 30 minutes.
[0066] (3) After transferring the mixture from step (2) into the reactor, place it in a 120°C oven and keep it warm for 12 hours. After natural cooling, wash, centrifuge, and dry for 24 hours.
[0067] (4) The sample obtained in step (3) is placed in a tube furnace and heated to 400℃ at a rate of 5℃ / min, and held at that temperature for 3h to obtain Fe2O3 / BaCo2Fe. 16 O 27 The composite material is denoted as Fe2O3 / BaCo2Fe. 16 O 27 -12h.
[0068] The material prepared in Example 3 was scanned using an X-ray diffractometer, and the results are shown below. Figure 1 It is Fe2O3 / BaCo2Fe 16 O 27 Composite materials.
[0069] The material prepared in Example 3 was tested using a scanning electron microscope, and the results are shown in the figure. Figure 2 In the middle (c), it can be seen that Fe2O3 is spindle-shaped and coated on BaCo2Fe. 16 O 27 surface.
[0070] Example 4: Preparation of Fe2O3 / BaCo2Fe 16 O 27 Composite materials
[0071] (1) BaCo2Fe was prepared according to the steps in Example 1. 16 O 27 ;
[0072] (2) Place 0.25g FeCl3·6H2O in 35mL of deionized water, and then add 0.4g of BaCo2Fe prepared in step (1). 16 O 27After mixing, stir for 30 minutes, add 35 mL of ethylene glycol, and continue stirring for another 30 minutes.
[0073] (3) After transferring the mixture from step (2) into the reactor, place it in a 120°C oven and keep it warm for 16 hours. After natural cooling, wash, centrifuge, and dry for 24 hours.
[0074] (4) The sample obtained in step (3) is placed in a tube furnace and heated to 400℃ at a rate of 5℃ / min, and held at that temperature for 3h to obtain Fe2O3 / BaCo2Fe. 16 O 27 The composite material is denoted as Fe2O3 / BaCo2Fe. 16 O 27 -16h.
[0075] The material prepared in Example 4 was scanned using an X-ray diffractometer, and the results are shown below. Figure 1 It is Fe2O3 / BaCo2Fe 16 O 27 Composite materials.
[0076] The material prepared in Example 4 was tested using a scanning electron microscope, and the results are shown in the figure. Figure 2 In the middle (d), it can be seen that Fe2O3 is spindle-shaped and coated on BaCo2Fe. 16 O 27 surface.
[0077] Example 5: Preparation of Fe2O3 / BaCo2Fe 16 O 27 Composite materials
[0078] (1) BaCo2Fe was prepared according to the steps in Example 1. 16 O 27 ;
[0079] (2) Place 0.25g FeCl3·6H2O in 35mL of deionized water, and then add 0.4g of BaCo2Fe prepared in step (1). 16 O 27 After mixing, stir for 30 minutes, add 35 mL of ethylene glycol, and continue stirring for another 30 minutes.
[0080] (3) After transferring the mixture from step (2) into the reactor, place it in a 120°C oven and keep it warm for 24 hours. After natural cooling, wash, centrifuge, and dry for 24 hours.
[0081] (4) The sample obtained in step (3) is placed in a tube furnace and heated to 400℃ at a rate of 5℃ / min, and held at that temperature for 3h to obtain Fe2O3 / BaCo2Fe. 16 O 27The composite material is denoted as Fe2O3 / BaCo2Fe. 16 O 27 -24h.
[0082] The material prepared in Example 5 was scanned using an X-ray diffractometer, and the results are shown below. Figure 1 It is Fe2O3 / BaCo2Fe 16 O 27 Composite materials.
[0083] The material prepared in Example 5 was tested using a scanning electron microscope, and the results are shown below. Figure 2 In the middle (e), we can see that Fe2O3 is spindle-shaped and coated on BaCo2Fe. 16 O 27 surface.
[0084] Example 6: Preparation of Fe2O3 / BaCo2Fe 16 O 27 Composite materials
[0085] (1) BaCo2Fe was prepared according to the steps in Example 1. 16 O 27 ;
[0086] (2) Place 0.25g FeCl3·6H2O in 35mL of deionized water, and then add 0.4g of BaCo2Fe prepared in step (1). 16 O 27 After mixing, stir for 30 minutes, add 70 mL of ethylene glycol, and continue stirring for another 30 minutes.
[0087] (3) After transferring the mixture from step (2) into the reactor, place it in a 120°C oven and keep it warm for 12 hours. After natural cooling, wash, centrifuge, and dry for 24 hours.
[0088] (4) The sample obtained in step (3) is placed in a tube furnace and heated to 400℃ at a rate of 5℃ / min, and held at that temperature for 3h to obtain Fe2O3 / BaCo2Fe. 16 O 27 The composite material is denoted as Fe2O3 / BaCo2Fe. 16 O 27 -66%.
[0089] The material prepared in Example 6 was scanned using an X-ray diffractometer, and the results are shown below. Figure 1 It is Fe2O3 / BaCo2Fe 16 O 27 Composite materials.
[0090] The material prepared in Example 6 was tested using a scanning electron microscope, and the results are shown in the figure. Figure 2In the middle (f), we can see that Fe2O3 is spindle-shaped and coated on BaCo2Fe. 16 O 27 surface.
[0091] Example 7: Preparation of BaCo2Fe 16 O 27 microwave absorber
[0092] Take the BaCo2Fe prepared in Example 1 16 O 27 0.21g and 0.09g of paraffin wax were melted and pressed into a 3mm thick ring with an outer diameter of 7.0mm and an inner diameter of 3.04mm. The electromagnetic parameters were measured using a vector network analyzer within the range of 2–18GHz. The test results are shown below. Figure 3 In (a), the absorption performance shows that there is almost no absorption performance within the 0-5 mm absorption thickness.
[0093] Example 8: Preparation of Fe2O3 / BaCo2Fe 16 O 27 microwave absorber
[0094] Take the BaCo2Fe prepared in Example 2 16 O 27 0.21g and 0.09g of paraffin wax were melted and pressed into a 3mm thick ring with an outer diameter of 7.0mm and an inner diameter of 3.04mm. The electromagnetic parameters were measured using a vector network analyzer within the range of 2–18GHz. The test results are shown below. Figure 3 In Figure (b), the absorption performance shows that the minimum reflection loss value of the 0-5mm absorbing thickness is -23.4dB, which has a certain absorbing effect.
[0095] Example 9: Preparation of Fe2O3 / BaCo2Fe 16 O 27 microwave absorber
[0096] Take the BaCo2Fe prepared in Example 3 16 O 27 0.21g and 0.09g of paraffin wax were melted and pressed into a 3mm thick ring with an outer diameter of 7.0mm and an inner diameter of 3.04mm. The electromagnetic parameters were measured using a vector network analyzer within the range of 2–18GHz. The test results are shown below. Figure 3 (c) shows that the minimum reflection loss is -27.2dB with a 0-5mm absorbing thickness, demonstrating excellent absorbing performance.
[0097] Example 10: Preparation of Fe2O3 / BaCo2Fe 16 O 27 microwave absorber
[0098] Take the BaCo2Fe prepared in Example 4 16 O 27 0.21g and 0.09g of paraffin wax were melted and pressed into a 3mm thick ring with an outer diameter of 7.0mm and an inner diameter of 3.04mm. The electromagnetic parameters were measured using a vector network analyzer within the range of 2–18GHz. The test results are shown below. Figure 3 In the middle (d), the absorption performance shows that the minimum reflection loss in the 0-5mm absorption thickness range is -34.3dB, which shows good absorption performance.
[0099] Example 11: Preparation of Fe2O3 / BaCo2Fe 16 O 27 microwave absorber
[0100] Take the BaCo2Fe prepared in Example 5 16 O 27 0.21g and 0.09g of paraffin wax were melted and pressed into a 3mm thick ring with an outer diameter of 7.0mm and an inner diameter of 3.04mm. The electromagnetic parameters were measured using a vector network analyzer within the range of 2–18GHz. The test results are shown in the figure. Figure 3 In Figure (e), the absorption performance shows that the minimum reflection loss is -13.05dB within the absorption thickness range of 0-5mm, indicating a certain absorption performance.
[0101] Example 12: Preparation of Fe2O3 / BaCo2Fe 16 O 27 microwave absorber
[0102] Take the BaCo2Fe prepared in Example 6 16 O 27 0.21g and 0.09g of paraffin wax were melted and pressed into a 3mm thick ring with an outer diameter of 7.0mm and an inner diameter of 3.04mm. The electromagnetic parameters were measured using a vector network analyzer within the range of 2–18GHz. The test results are shown below. Figure 3 In Figure (f), the absorption performance shows that the minimum reflection loss in the 0-5mm absorption thickness range is -39.0dB, demonstrating good absorption performance.
[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A ferrite composite material, characterized in that, Including W-type ferrite BaCo2Fe 16 O 27 and coated in the W-type ferrite BaCo2Fe 16 O 27 Spindle-shaped Fe2O3 on the surface; The preparation method of the ferrite composite material includes the following steps: W-type ferrite BaCo2Fe 16 O 27 Powder, Fe 3+ A hydrothermal reaction is carried out with a mixture of salt, water, and ethylene glycol to obtain Fe₂O₃ / BaCo₂Fe. 16 O 27 Precursor; the hydrothermal reaction is carried out at a temperature of 100~150℃ for a time of 4~24h; The Fe2O3 / BaCo2Fe 16 O 27 The precursor is calcined to obtain the ferrite composite material; the calcination is carried out in an air atmosphere.
2. The ferrite composite material according to claim 1, characterized in that, The mass of the spindle-shaped Fe2O3 is W-type ferrite BaCo2Fe. 16 O 27 The mass is 0-10%, and the mass of the spindle-shaped Fe2O3 is not 0.
3. The method for preparing the ferrite composite material according to claim 1 or 2, characterized in that, Includes the following steps: W-type ferrite BaCo2Fe 16 O 27 Powder, Fe 3+ A hydrothermal reaction is carried out with a mixture of salt, water, and ethylene glycol to obtain Fe₂O₃ / BaCo₂Fe. 16 O 27 Precursor; the hydrothermal reaction is carried out at a temperature of 100~150℃ for a time of 4~24h; The Fe2O3 / BaCo2Fe 16 O 27 The precursor is calcined to obtain the ferrite composite material; the calcination is carried out in an air atmosphere.
4. The preparation method according to claim 3, characterized in that, The Fe 3+ The salt includes FeCl3·6H2O; the Fe 3+ Salt and W-type ferrite BaCo2Fe 16 O 27 The mass ratio of the powder is (1~5):
4.
5. The preparation method according to claim 3 or 4, characterized in that, The water and Fe 3+ The salt dosage ratio is 35 mL: 0.25 g; the volume ratio of ethylene glycol to water is (0~70): 35, and the volume of ethylene glycol is not 0.
6. The preparation method according to claim 3, characterized in that, The calcination temperature is 350~500℃, and the time is 3~5h.
7. The preparation method according to claim 3, characterized in that, The W-type ferrite BaCo2Fe 16 O 27 The powder preparation method includes the following steps: (a) Barium nitrate, cobalt nitrate, ferric nitrate, water, and citric acid are mixed to form a sol-gel, resulting in a wet gel; the barium nitrate, cobalt nitrate, and ferric nitrate are respectively dissolved in Ba... 2+ Co 2+ and Fe 3+ The Ba 2+ Co 2+ and Fe 3+ The molar ratio is 1:2:15.3; (b) The wet gel is dried and then calcined to obtain the W-type ferrite BaCo2Fe. 16 O 27 powder.
8. The preparation method according to claim 7, characterized in that, In step (a), Ba 2+ Co 2+ and Fe 3+ The ratio of the total molar amount to the molar amount of citric acid is 1:(1~1.5). The calcination in step (b) includes a first calcination and a second calcination in sequence. The temperature of the first calcination is 450°C and the holding time is 3h. The temperature of the second calcination is 1300°C and the holding time is 3h.
9. The application of the ferrite composite material according to claim 1 or 2 or the ferrite composite material prepared by the preparation method according to any one of claims 3 to 8 as a microwave absorber.
Citation Information
Patent Citations
Method for preparing spindle shaped alpha-Fe2O3 powder
CN101293674A